INSECTICIDAL AND PHYTOCIDAL EFFECTS OF SIMMONDSIA CHINENSIS CONSTITUENTS - Ahmed S. Abdel-Aty (Journal of Animal and Plant Sciences, 2018)
Simmondsia chinensis seeds were extracted subsequently with different solvent systems. Seven resulted fractions were th evaluated for their insecticidal activity against Culex pipiens 4 instar larvae and phytocidal activity on wheat. All fractions killed the treated larval population increasingly with increasing time of exposure and concentration. Fractions 1, 2, 6 and 7 caused LC equaled 463.6 and 296.4 µg/ml; 321 and 166.8 µg/ml; 403 and 292 µg/ml and 1100 and 927.7 50 µg/ml after 24 and 48 hours exposure, respectively. Fraction 5 was less effective. Fractions 3 and 4 were the most effective achieving LC values equaled 59.6 and 32.6 µg/ml comparing with 27 and 23.7µg/ml after 24 and 48 hours 50 exposure, respectively. The phytocidal effect on wheat (T. aestivum) seeds was differed in systematic arrangement with increasing the concentration. Seed germination was inhibited by fractions 4, 5 and 7 slightly with EC values equaled > 50 2000 µg/ml. Fractions 1, 2, 3 and 6 moderately inhibited the seed germination with EC values equaled 347, 505, 541.6 50 and 723.2 µg/ml, respectively. The tested fractions harshly inhibited both root and shoot systems growth. Generally these fractions appeared to be more active on the shoot systems. Treatment of the pre-germinated seeds with these fractions reduced the growth inhibitions of root and shoot systems. The active fractions constituents were identified through GC- MS analysis. The major contained fatty acids were 11-ecosenic acid (C H O , 20.563%) and 5,13-docosadienoic acid 20 38 2 ( C H O , 13.620%) in fraction 3, however erucic acid (C H O , 40.279%) and arachidic acid (C H O , 24.517%) 22 40 2 22 42 2 20 40 2 were the major contents of fraction 4. Some other fatty acids at 5.3448.956% and 2.4018.934% in fractions 3 and 4, respectively were differently identified proving the differences in their biological effects. oil, protein and carbohydrate contents in jojoba seeds
Keywords: Simmondsia chinensis; Phytocidal; Insecticidal; Fatty acids; Identification